Occupational Asthma: The Knowledge Needs for a Better Management - Rui, Francesca; Otelea, Marina Ruxandra; Fell, Anne Kristin Møller; Stoleski, Sasho; Mijakoski, Dragan; Holm, Mathias; Schlünssen, Vivi; Larese Filon, Francesca (Oxford University Press (OUP), 2022)
The management of occupational asthma (OA) may be influenced by several factors and removal from exposure is the main tertiary prevention approach, but it is not always feasible without personal and socioeconomic consequences. Reducing the delay between the onset of suggestive symptoms of OA and the diagnosis of OA is associated with a better prognosis. Workers' education to increase awareness to trigger agents and a medical surveillance program directed especially at at-risk workers could be helpful in reducing this latency time. An early identification of workers who develop rhinitis and conjunctivitis which often precede the onset of asthma symptoms could be important for an early identification of OA. This is particularly important for cases of asthma caused by high-molecular-weight sensitizers and in the early years of employment. The availability of financial support and compensation measures for workers with OA may influence the latency time before diagnosis and, consequently, may influence the OA outcomes. In conclusion, there is a need for high-quality cohort studies that will increase knowledge about risk factor that may influence the timing of diagnosis of OA. This knowledge will be useful for implementation of future surveillance and screening programs in workplaces.
Keywords: management; professional asthma; surveillance